Efecto comparativo de cultivares de Pisum sativum l. “arveja verde” en rendimiento, bajo condiciones del valle Colca Huari, Áncash - Collazos Jacinto, Lenin Felipe (2020)
Objective: To determine the comparative effect of varieties of Pisum sativum L. “Green pea” in yield, i n conditions of the Colca Huari, Áncash. Methodology: the present investigation was developed under the environmental conditions of said valley, during May and September 2019. The factors in study were six varieties´s green peas:white Creole, quantum, pigeon breast, alderman, auction and blue, sowing 30 cm between plants and 80 cm between furrows, three seeds per stroke, the variables evaluated: emergency percentage, vegetative vigor, plant height, leaf length, leaf width, number of leaves, number of buttons per plant, number of pods per plant, pod length, green pea yield in t.ha-1. The complete randomized block design with 6 treatments and 3 repetitions was used. Results: The characteristic emergency percentage fluctuates in 4 days, from the treatment of the lowest percentage T3 to the highest percentage of emergency treatment T6. While the vigor fluctuates in 1 unit between the lowest T2 and the best T4 vigor. For plant height it fluctuates in 27 cm, between the smallest treatment T1 and the largest treatment T6, the characteristic of leaf length fluctuates between 9.23 and 9.60 cm. on average, between the lowest white Creole treatment and the largest blue treatment. The green pea yield characteristic in t.ha-1 fluctuates between 1.95 and 3.22 t.ha-1 on average, between the lowest Creole white treatment and the largest blue treatment. Conclusions: In Performance there was a highly significant statistical response between treatments, grouping them in the first place the T6 blue variety treatment, the T5 variety auction treatment and the T4 alderman variety treatment, alternative to improve performance